The Syk-Coupled C-Type Lectin Receptors Dectin-2 and Dectin-3 Are Involved in Paracoccidioides brasiliensis Recognition by Human Plasmacytoid Dendritic Cells - Preite, Nycolas Willian; Feriotti, Claudia; Souza de Lima, Dhêmerson; da Silva, Bruno Borges; Condino-Neto, Antônio; Pontillo, Alessandra; Calich, Vera Lúcia Garcia; Loures, Flávio Vieira (Frontiers in Immunology, 2018)
Plasmacytoid dendritic cells (pDCs), which have been extensively studied in the context of the immune response to viruses, have recently been implicated in host defense mechanisms against fungal infections. Nevertheless, the involment of human pDCs during paracoccidiodomycosis (PCM), a fungal infection endemic to Latin America, has been scarcerly studied. However, pDCs were found in the cutaneous lesions of PCM patients, and in pulmonary model of murine PCM these cells were shown to control disease severity. These findings led us to investigate the role of human pDCs in the innate phase of PCM. Moreover, considering our previous data on the engagement of diverse TLRs and CLRs receptors in P. brasiliensis recognition, we decided to characterize the innate immune receptors involved in the interaction between human pDCs and yeast cells. Purified pDCs were obtained from peripheral blood mononuclear cells from healthy donors and they were stimulated with P. brasiliensis with or without blocking antibodies to innate immune receptors. Here we demonstrated that P. brasiliensis stimulation activates human pDCs that inhibit fungal growth and secrete pro-inflammatory cytokines and type I IFNs. Surprisingly, P. brasiliensis-stimulated pDCs produce mature IL-1β and activate caspase 1, possibly via inflammasome activation, which is a phenomenon not yet described during pDC engagement by microorganisms. Importantly, we also demonstrate that dectin-2 and dectin-3 are expressed on pDCs and appear to be involved (via Syk signaling) in the pDC-P. brasiliensis interaction. Moreover, P. brasiliensis-stimulated pDCs exhibited an efficient antigen presentation and were able to effectively activate CD4+ and CD8+ T cells. In conclusion, our study demonstrated for the first time that human pDCs are involved in P. brasiliensis recognition and may play an important role in the innate and adaptive immunity against this fungal pathogen.